Vision science and adaptive optics, the state of the field - Marcos, S; Werner, JS; Burns, SA; Merigan, WH; Artal, P; Atchison, DA; Hampson, KM; Legras, R; Lundstrom, L; Yoon, G; Carroll, J; Choi, SS; et al. (Elsevier, 2017)
Adaptive optics is a relatively new field, yet it is spreading rapidly and allows new questions to be asked about how the visual system is organized. The editors of this feature issue have posed a series of question to scientists involved in using adaptive optics in vision science. The questions are focused on three main areas. In the first we investigate the use of adaptive optics for psychophysical measurements of visual system function and for improving the optics of the eye. In the second, we look at the applications and impact of adaptive optics on retinal imaging and its promise for basic and applied research. In the third, we explore how adaptive optics is being used to improve our understanding of the neurophysiology of the visual system.